Social Media as a Crisis Communication Tool During the 2021 KwaZulu-Natal and Gauteng Civil Unrest - Luthando Valencia Ngubane; Elvis Madondo (Language, Technology, and Social Media, 2026)
This study examines how social media functioned as a crisis communication and mobilisation infrastructure during the July 2021 civil unrest in KwaZulu-Natal and Gauteng, South Africa. Although prior research has linked digital platforms to protest organisation and crisis information flows, less attention has been paid to how affected publics perceived the simultaneous roles of mobilisation, risk communication, official communication, and misinformation in the South African unrest. Using a quantitative survey design, data were collected with an online questionnaire from 299 adult social media users who resided in KwaZulu-Natal, had witnessed the unrest through social media, and consented to participate. Descriptive statistics, reliability testing, exploratory factor analysis, and chi-square tests were used to analyse the data. The instrument showed high internal consistency (Cronbach’s alpha = 0.851). Findings indicate that respondents strongly perceived social media as an integral communication channel, a tactical source of real-time information, and a mechanism for broadcasting the unrest beyond local communities. Four dimensions emerged from the analysis: connectivity and information sharing, safety and risk communication, official crisis communication, and public engagement and mobilisation. Gender differences were statistically significant for social media as a crucial information source and for real-time coordination, while race-based patterns suggested uneven perceptions across several items. The study contributes a contextualised crisis-informatics perspective on the dual capacity of social media to support public safety and intensify disorder during civil unrest.